2021
DOI: 10.1186/s13195-021-00859-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversible GABAergic dysfunction involved in hippocampal hyperactivity predicts early-stage Alzheimer disease in a mouse model

Abstract: Background Neuronal hyperactivity related to β-amyloid (Aβ) is considered an early warning sign of Alzheimer disease (AD). Although increasing evidence supports this opinion, the underlying mechanisms are still unknown. Methods Here, we recorded whole-cell synaptic currents and membrane potentials using patch clamping of acute hippocampal slices from human amyloid precursor protein (APP)/presenilin-1 transgenic (5XFAD) mice and their wild-type litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Cognition and memory require carefully balanced excitatory and inhibitory activity ( Zhou and Yu, 2018 ). In different AD mouse models, impairments in inhibition precede plaque formation, disrupting brain rhythms associated with memory formation ( Arroyo-García et al, 2021 ; Li et al, 2021 ; Nuriel et al, 2017 ; Sederberg et al, 2006 ). Modified inhibitory tone in early AD is likely related to changes in the intrinsic excitability of local circuit inhibitory interneurons.…”
Section: Introductionmentioning
confidence: 99%
“…Cognition and memory require carefully balanced excitatory and inhibitory activity ( Zhou and Yu, 2018 ). In different AD mouse models, impairments in inhibition precede plaque formation, disrupting brain rhythms associated with memory formation ( Arroyo-García et al, 2021 ; Li et al, 2021 ; Nuriel et al, 2017 ; Sederberg et al, 2006 ). Modified inhibitory tone in early AD is likely related to changes in the intrinsic excitability of local circuit inhibitory interneurons.…”
Section: Introductionmentioning
confidence: 99%
“…This physical limitation has been overcome with the invention of super-resolution microscopes, which work around it in several different ways and offer spatial resolutions similar to that of electron microscopes [100]. The second limit is that high spatial resolution can only be achieved at a low temporal resolution and vice versa, meaning live processes can only be visualized at a low spatial resolution, and only dead tissue or cells can be used for high-resolution studies [15]. As we have shown here, this second limit still requires some compromise in terms of spatial resolution if the high temporal resolution is required and vice versa (Figure 3) but is also becoming resolved with the availability of super-resolution microscopes for live cells (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…These are important avenues of future inquiry, as they may provide insight into the mechanism driving the sex-specific effects found, and future studies should directly test the role of these factors in the relationship between GABA+ concentration and episodic memory in women. Third, while it is not possible to determine from the 1 H MRS estimate where the GABA signal originates, as the measurement reflects a combination of synaptic, intracellular, and extrasynaptic GABA from all types of GABAergic interneurons in our right hippocampal region of interest (Maddock and Buonocore, 2012), the findings reported by Li et al (2021) suggest that hippocampal CA1 GABA A postsynaptic pyramidal neuron receptors might be a likely source. Future studies using PET imaging could provide clarity on the precise coupling of the source of the GABA signal and its association with episodic memory deficits.…”
Section: Limitationsmentioning
confidence: 91%
“…However, animal models have shown that GABA plays a critical role in long-term memory formation by synchronizing pyramidal neuron activity (Paulsen and Moser, 1998;Lucas and Clem, 2018) and by preventing hyperactivity in the hippocampus (Najm et al, 2019), a brain structure critical for episodic memory formation and retrieval (Nyberg et al, 1996;Schacter et al, 1996). A study by Li et al (2021) recently showed, using a 5XFAD AD-mouse model, that hyperactivity of pyramidal neurons in the CA1 field of the hippocampus was driven by GABA A receptor-mediated inhibitory synaptic decline, preceded Aβ-related pathology, was accompanied by cognitive impairments in an episodic-like memory task, and could be reversed via administration of a GABA A receptor agonist (Li et al, 2021). In humans, electrophysiological hyperactivity in the hippocampus-a brain structure that undergoes early and significant morphologic changes in AD (Putcha et al, 2011)-presages episodic memory decline in individuals at-risk for AD (Dickerson et al, 2005;Hämäläinen et al, 2007;Sperling et al, 2010;Yassa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%